The result of surgical interventions in women with recurrent prolapse of the vagina posterior segment - Banakhevich, R. M.; Barkovsky, D. E. (Zaporozhye Medical Journal, 2014)
Aim. 44 women with recurrent genital prolapse of the posterior segment of the vagina were examined and treated. Results of different types of synthetic implants were evaluated. Methods and results. 26 patients underwent transvaginal mesh with implant. In 18 patients implant Prolift posterior™ was used. The paper presents the features of the application and possible complications of the use of synthetic implants to correct the fascial defects of the posterior vaginal wall. Intraoperative bleeding after Prolift posterior™ installing were observed in 5.6 % of patients, that was lower than in the control group –7,7% (p<0,05). Extensive subcutaneous hematoma was observed in 88,7% of patients after installation of the Prolift posterior™, in the comparison group – in 15,4% of patients. Wounding anterior rectal wall was observed only in 1 (5,6%) case when Prolift posterior™was installed. Conclusion. The analysis of the causes of postoperative complications and their prevention methods proposed. Recurrence after surgery with the use of synthetic materials in the operated segment was not observed.